Communities of Practice for Local Capacity in Central Asia : The Community Empowerment Network - Caldwell Johnson, Erik (World Bank, Washington, DC, 2012)
In 2002 the World Bank Institute and Europe and Central Asia Region (ECA) launched the Community Empowerment Network (CEN): four national networks linked through regional activities that would build the capacity of communities and development partners to implement community-driven development (CDD) projects. CEN has to date had clear successes as well as difficulties-particularly in linkage to World Bank operations and improving local coordination with multiple donors. CEN's experience points to specific lessons that could be applied in creating other communities of practice, for example, emphasizing peer review among countries and establishing clear indicators of progress as well as a number of specific administrative lessons.